2019
DOI: 10.1155/2019/1850462
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of an Antimitotic and a Bromodomain 4 Inhibitor Synergistically Inhibits the Metastatic MDA-MB-231 Breast Cancer Cell Line

Abstract: Current chemotherapeutic agents have many side effects and are toxic to normal cells, providing impetus to identify agents that can effectively eliminate tumorigenic cells without damaging healthy cells. The aim of this study was to examine whether combining a novel BRD4 inhibitor, ITH-47, with the antimitotic estradiol analogue, ESE-15-ol, would have a synergistic effect on inhibiting the growth of two different breast cancer cell lines in vitro. Our docking and molecular dynamics studies showed that compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…ESE-15-ol is a microtubule-targeting agent, which interferes with normal formation of mitotic spindle and thus leads to mitotic arrest [76]. ITH-47 BRD4-selective inhibitor showed synergistic activity with ESE-15-ol in TNBC cells [77].…”
Section: Antimitotic Estradiol Analogue (Ese-15-ol)mentioning
confidence: 99%
“…ESE-15-ol is a microtubule-targeting agent, which interferes with normal formation of mitotic spindle and thus leads to mitotic arrest [76]. ITH-47 BRD4-selective inhibitor showed synergistic activity with ESE-15-ol in TNBC cells [77].…”
Section: Antimitotic Estradiol Analogue (Ese-15-ol)mentioning
confidence: 99%
“…The table reports the drug, its target with PDB ID, in silico/in vitro/in vivo methods used to test the drug, clinical trials, mechanism of action and reference. In another study [68], the authors investigated the combination of two novel compounds, namely, ITH-47 (a BRD4 inhibitor) and ESE-15-ol (an antimitotic agent). The in vitro study revealed that the combination of these two compounds inhibits the growth of MDA-MB-231.…”
Section: Combination Of Drugsmentioning
confidence: 99%
“…To compare the binding energy of the two molecules, they performed molecular docking with a known drug-i.e., JQ1-which revealed that, compared to JQ1, the molecules can achieve similar binding energies and sites as bromodomain-containing protein 4 (BRD4). BRD4 plays a role in regulating c-Myc, a key regulator of cell growth and apoptosis [68].…”
Section: Combination Of Drugsmentioning
confidence: 99%